2022
DOI: 10.1111/joim.13406
|View full text |Cite
|
Sign up to set email alerts
|

Hypocretins (orexins): The ultimate translational neuropeptides

Abstract: The hypocretins (Hcrts), also known as orexins, are two neuropeptides produced exclusively in the lateral hypothalamus. They act on two specific receptors that are widely distributed across the brain and involved in a myriad of neurophysiological functions that include sleep, arousal, feeding, reward, fear, anxiety and cognition. Hcrt cell loss in humans leads to narcolepsy with cataplexy (narcolepsy type 1), a disorder characterized by intrusions of sleep into wakefulness, demonstrating that the Hcrt system i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(80 citation statements)
references
References 247 publications
1
62
0
1
Order By: Relevance
“…As previously described above, studies on pathophysiological roles of orexins and their receptors are focused on CNS ( 7 ) and mainly narcolepsy type I pathology ( 60 ). Moreover, a lot of studies also revealed the impact of orexins on addiction, neuro-inflammation associated to the microglia and neurodegenerative diseases including Alzheimer’s disease ( 11 , 61 , 62 ).…”
Section: Anti-tumoral Properties Of Orexins and Receptor Antagonist A...mentioning
confidence: 99%
See 2 more Smart Citations
“…As previously described above, studies on pathophysiological roles of orexins and their receptors are focused on CNS ( 7 ) and mainly narcolepsy type I pathology ( 60 ). Moreover, a lot of studies also revealed the impact of orexins on addiction, neuro-inflammation associated to the microglia and neurodegenerative diseases including Alzheimer’s disease ( 11 , 61 , 62 ).…”
Section: Anti-tumoral Properties Of Orexins and Receptor Antagonist A...mentioning
confidence: 99%
“…The major physiological action ( Figure 1 ) in central nervous system (CNS) of the orexins/OXR system, widely studied for over 20 years, was to maintain wakefulness ( 6 , 7 ). The main pathology associated to this action was the narcolepsy type I characterized by excessive daytime sleepiness (EDS) associated to Rapid Eye Movement (REM) symptoms including cataplexy, hallucinations, sleep paralysis and fragmentation of night sleep ( 7 , 8 ). This rare neurological disorder was caused by the loss of orexin neurons leading to the absence of orexins secretion ( 7 ) but in dog, this disorder was related to orexin receptor mutation ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 24–28 , 36–39 For example, manipulations of the Orx-S simultaneously modulate neurotransmitters associated with alertness and wakefulness (ie, dopamine, norepinephrine, acetylcholine, and histamine). 27 …”
Section: Orexins/hypocretinsmentioning
confidence: 99%
“…Ox2R mRNA in the adrenal cortex of male rats indicates orexin's involvement in the synthesis and/or release of adrenal steroids ( 17 ). Regarding the development of PTSD, low orexin tone during stressful events has been proposed to be associated with increased risk ( 67 ). Orexin's proposed role in TTS pathophysiology might be similarly understood.…”
Section: Alternative Explanatory Framework For Pathophysiology Of Tts...mentioning
confidence: 99%